Demonstration of Photoelectrochemical‐Type Photodetectors Using Seawater as Electrolyte for Portable and Wireless Optical Communication. Issue 10 (23rd March 2022) - Luo, Yuanmin; Wang, Danhao; Kang, Yang; Liu, Xin; Fang, Shi; Memon, Muhammad Hunain; Yu, Huabin; Zhang, Haochen; Luo, Dongyang; Sun, Xiyu; Ooi, Boon S.; Gong, Chen; et al.
Abstract: The emerging photoelectrochemical‐type photodetector (PEC‐PD), because of its unique device architecture by using an aqueous electrolyte, is naturally applicable in the pursuit of underwater optical communication without sophisticated device packaging and assembling. Unfortunately, the traditional PEC detecting process typically involves a large electrochemical workstation with long cables and wire connections for photo signal acquisition, which hinders its applications in wireless optical communication. In this work, an AlGaN nanowire‐based self‐powered PEC‐PD is fabricated that uses seawater as an electrolyte, and then an optical communication system including the PEC‐PD and a portable electrochemical workstation as the signal receiver for data communication is built. Essentially, the self‐power PEC‐PD shows a high responsivity of −15.5 mA W –1, a fast response/recovery time of ≈100 ms, and high stability operation in the seawater electrolyte. Foremost, the optical communication system shows high accuracy in wireless transmission of ASCII code signals in a seawater environment. Such a demonstration offers a new device architecture for possible under‐seawater communication systems by leveraging the unique operation principle of photoelectrochemical devices in the future. Abstract : An optical communication system for wireless photocurrent signal transmission in seawater environment is reported, which is composed of a semiconductor AlGaN nanowire‐based self‐powered photoelectrochemical‐type photodetector (PEC‐PD) that is equipped with a portable electrochemical workstation. Such a PEC‐PD device architecture possibly provides a new device architecture for next‐generation wireless under‐seawater communication systems.